Carbon Dynamics Along the Seine River Network: Insight From a Coupled Estuarine/River Modeling Approach - Laruelle, Goulven G.; Marescaux, Audrey; Le Gendre, Romain; Garnier, Josette; Rabouille, Christophe; Thieu, Vincent (Frontiers in Marine Science, 2019)
The Seine River discharges over 700 Gg of carbon (C) every year into the sea mostly under the form of Dissolved Inorganic Carbon (DIC) and emits 445 Gg under the form of carbon dioxide (CO2) to the atmosphere over its entire river network. The watershed, which drains 76,000 km2, is heavily populated with 18 106 inhabitants and is thus submitted to large anthropic pressure. The offline coupling of two Reactive Transport Models is used to understand the complex spatial and temporal dynamics of carbon, oxygen and nutrients and quantify the CO2 exchange at the air-water interface along the main axis of the river. The estuarine section of the Seine is simulated by the generic estuarine model C-GEM (for Carbon Generic Estuarine Model), while the upstream part of the network, devoid of tidal influence is simulated by the pyNuts-Riverstrahler modeling platform which also includes an explicit representation of the drainage network ecological functioning. Our simulations provide a process-based representation of nutrients, oxygen, total organic carbon (TOC) and the carbonate system (DIC and alkalinity) over the entire year 2010. Our coupled modelling chain allows quantifying the respective contributions of the estuarine and freshwater sections of the system in the removal of carbon as well as following the fate of TOC and DIC along the river network. Our results also allow calculating an integrated carbon budget of the Seine river network for year 2010.